TPSACK framework development in measuring the technological, pedagogical, skills, and content knowledge of the art and design education students / Roslaili Anuar ... [et al.] - Anuar, Roslaili; Abdullah, Muhammad Azhar; Wan Zakaria, Wan Zamani; Nik Aziz, Nik Nor Azidah; Ramli, Harozila; Said, Tajul Shuhaizam (2022)
The emergence of a change in the Malaysian education system involving learning methods based on the use of technology is growing increasingly in line with technological development involving 21st-century learning. Learning with technology has become more relevant to the emergence of change in the Malaysian education system. High technology development now allows information to move unlimited and provides no boundaries. Universities are the main centre for producing competent, efficient, and computer literate students to meet the demands of today’s work industry. The advent of ICT in this age of borderless communication has brought innovation to the university students teaching and learning styles to a new level. This scenario affects the visual art area which involves the Art and Design Education (ADE) program at the Faculty of Education, Universiti Teknologi MARA. The educators bear a heavy responsibility in helping the government accomplish its objectives in the 9th Malaysian Plan, namely to generate excellent future generations.